QSAR Modeling of RET Kinase Inhibitors Based on Structure from 49 Various 5, 6-Fused Bicyclic Hetero aromatic Cores for Patent-Driven Verification. - Rahul B. Lovhare; Dinesh N. Pawar; Jagruti R. Shewale; Bhavana R. Vasave; Shradha K. Patel (International Journal of Pharmacy and Analytical Research, 2025)
The receptor tyrosine that is rearranged during transfection (RET) Kinase is essential for the growth of the enteric genitourinary tissues and the nervous system. 1 Research on cancer found that RET is a carcinogenic factor in nonsmall-cell lung cancer (NSCLC),2 RET changes show a strong correlation with different types of cancer. 3 The turning on of down- stream pathways like MAPK and PI3K/AKT, which are found in the RET fusion protein tyrosine kinase, originates from Autophosphorylation and ligand-independent homodimerization brought about by the intrachromosomal rearrangement of RET.3 The optimal QSAR model exhibited high predictive performance, with R2 (of training data) and Q2 (of test data) values of 0.801 and 0.794, respectively, effectively predicting known inhibitors. The optimal model was doubly verified by patent-filed RET inhibitors as the out-of-set data to demonstrate acceptable residual analysis results. Moreover, feature importance analysis of the QSAR model outlined the impact of substituent characteristics on the inhibitory activity within the 5,6- fused bicyclic heteroaromatic core structures. Furthermore, the relationship between structure and inhibitory activity was successfully applied to the RET screening of known clinical and nonclinical kinase inhibitors to afford accurate off-target prediction.